The Influence of the Microbiome on Early-Life Severe Viral Lower Respiratory Infections and Asthma—Food for Thought? - Lynch, Jason P.; Sikder, Md. Al Amin; Curren, Bodie F.; Werder, Rhiannon B.; Simpson, Jennifer; Cuív, Páraic Ó; Dennis, Paul G.; Everard, Mark L.; Phipps, Simon (Frontiers in Immunology, 2017)
Severe viral lower respiratory infections are a major cause of infant morbidity. In developing countries, respiratory syncytial virus (RSV)-bronchiolitis induces significant mortality, whereas in developed nations the disease represents a major risk factor for subsequent asthma. Susceptibility to severe RSV-bronchiolitis is governed by gene-environmental interactions that affect the host response to RSV infection. Emerging evidence suggests that the excessive inflammatory response and ensuing immunopathology, typically as a consequence of insufficient immunoregulation, leads to long-term changes in immune cells and structural cells that render the host susceptible to subsequent environmental incursions. Thus, the initial host response to RSV may represent a tipping point in the balance between long term respiratory health or chronic disease (e.g. asthma). The composition and diversity of the microbiota, which in humans stabilises in the first year of life, critically affects the development and function of the immune system. Hence, perturbations to the maternal and/or infant microbiota are likely to have a profound impact on the host response to RSV and susceptibility to childhood asthma. Here, we review recent insights describing the effects of the microbiota on immune system homeostasis and respiratory disease, and discuss the environmental factors that promote microbial dysbiosis in infancy. Ultimately, this knowledge will be harnessed for the prevention and treatment of severe viral bronchiolitis as a strategy to prevent the onset and development of asthma.